Diagnosis and management of pancreatic exocrine insufficiency. Issue 9 (22nd May 2013) - Kumar, Mayur; Wilkinson, Mark
Abstract Managing pancreatic exocrine insufficiency effectively is challenging for both specialist and primary‐care physicians. This review summarises current methods employed to diagnose and treat PEI effectively and prevent complications.